Innovative Digital Practices: Enhancing the Effectiveness of Human Resource Management in the Digital Transformation Era - Hassani , Omar; Boubegra , Nacer (Finance and Business Economies Review, 2023)
This study explores the role of digital transformation in enhancing human resource management within organizations. It employs a descriptive methodology to examine various dimensions and applications of digital transformation in the field of human resource management. The findings highlight the importance of digital transformation for maintaining competitiveness and efficacy in today's business landscape. The study emphasizes the need for an organizational strategy focused on digital transformation as a primary objective, along with a meticulous plan for its efficient execution. Overall, digital transformation is seen as a crucial factor in elevating and refining human resources practices.